Failure Analysis of Landing Gear Material - Lubay, Asmadi; Afriany, Reny; Ilmi, Bahrul; Pusvyta, Yeny (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2024)
The electroplating process of ferrous and non-ferrous metals has advantages such as; as a protector against corrosion, improving appearance and increasing hardness, for example in coating: Cr, Cd and Ni. However, the coating process with Cd on AISI 4340 steel can result in metal embrittlement which leads to delayed brittle failure. This damage is very dangerous because there is no previous indication on the metal surface. In addition, fracture can occur at stresses much lower than the tensile stress of the material. From the results of this study, it is known that the non-uniformity of the thickness of the Cd layer formed results in stress concentration which further forms strain, this factor triggers the initial crack. The embrittlement by hydrogen comes from the electroplating bath that uses conventional cyanide coupled with brighteners. In addition, the very hard nature of AISI 4340 steel contributes to the embrittlement. The embrittlement of the material by hydrogen is caused by the presence of elemental sulphur which is cathodic poisons that segregate at the grain boundaries. Hardness will decrease the higher the baking temperature and the longer the baking time. The best condition to prevent embrittlement is if the baking process is carried out for at least 48 hours at a temperature of 250°C. The fracture surface by hydrogen embrittlement is in the form of intergranular crack, which indicates that the fracture is brittle.